Using Propensity Score Matching Technique to Estimate Utilization and Costs of General Practitioners’ Services associated with Alzheimer’s Disease - Rajan Sharma; Elizaveta Sopina; Jan Sørensen (Journal of Health Economics and Outcomes Research)
**Objective:** General practitioners (GPs) play an important role in caring for people with Alzheimer’s disease (AD). However, the cost and the extent of service utilization from GPs due to AD patients are difficult to assess. This study aimed to explore the principles of propensity score matching (PSM) technique to assess the additional GP service use and cost imposed by AD in persons aged ≥60 years in Denmark.